PERAN PEMBELAJARAN IPS DALAM PEMBENTUKAN KARAKTER SISWA SD - Ni Made Griyanthi; Ni Luh Raka Apsari; Ni Kompiang Puspadhini (Cahaya Ilmu Bangsa Institute, 2024)
The flow of globalization also has a negative impact on people's lives, namely the erosion of character values ​​among Indonesia's young generation. If this behavior is allowed, the Indonesian people will lose their identity and unique characteristics as a nation that is friendly, polite, ethical and full of a sense of family. This shift in values ​​and morals needs to be observed because it is the root cause of changes in the nation's character. Character education is expected to be a solution offered in resolving problems involving juvenile delinquency. Character formation, especially of the younger generation, requires the role of schools. Schools as formal institutions that develop the younger generation need to plan the implementation of conceptual social studies learning, so that it can be more effective in forming character. Social studies learning has a strategic role in character formation. Character education has the same direction and goals as social studies learning objectives, both of which aim to develop students into good citizens. Through character education, students are expected to become good citizens guided by religion, traditions and values ​​according to Indonesian culture. Therefore, it is necessary to develop values ​​that are part of students' lives, namely the values ​​of faith and devotion, nationalism, patriotism, responsibility, honesty, caring, discipline and independence.